Типіфікація видів роду Puccinellia Parl. (Poaceae), описаних з території України - Федорончук, М.М.; Губарь, Л.М.; Футорна, О.А. (Український ботанічний журнал, 2012)
Указаны и типифицированы пять видов рода Рuccinellia Рarl. (Poaceae), описанных с территории Украины. Для каждого из них приведены основная синонимика, номенклатурный тип (по протологу и голотип, изотип, лектотип или изолектотип, синтип, неотип), указаны автор вида и место хранения. Five species of the genus Рuccinellia Рarl. (Poaceae) described from Ukraine are typified. The following data for each species are provided: basionym, original nomenclatural citation; holotype according to protologue, or isotype, lectotype, syntype, neotype; herbarium(-a) in which the specimen(s) is(are) deposited.